ISLAM DAN DEMOKRASI: ANALISIS TAFSIR MAUDHU’I - Sri Asti Andani; Salman Izzulhaqq; Wina Nurhaena (Melati Institute, 2023)
Democracy remains a controversial issue today among thinkers. As a religion, conceptually Islam contains many teachings. Islam teaches its people to conduct discussion in solving existing problems in order to get the best decisions and results. In this article, the author seeks to analyze and explain how democracy is in Islamic view by referring to several verses in the Qur'an. The author uses the maudhu'i tafsir approach, namely by collecting related verses, expressing asbab an-nuzul, and plausibility of the verses. Among the results of this study are several verses related to the principle of democracy, one of which is the word Shura or discution, contained in Qs. Al-Baqarah verse 233, Qs. Ali-Imran verse 159, and Qs. Ash-Shura verse 38. Islam can be said to have compatibility with democracy because there are common values that can be applied, such as justice, deliberation and equality.